Leadership and Integrity The Citadels for Constitutionalism in Kenya - Peter Kwenjera (PÁZMÁNY LAW REVIEW, 2023)
Chapter 6 of the Constitution of Kenya, 2010 provides for the modicum of constitutionalism that state officers ought to espouse in exercising public authority. Kenya has a robust legal and institutional framework that is mandated to implement the provisions of Chapter 6 of the 2010 Constitution in remedying historical accounts of corruption among state officials. This article appraises the strides made and the notable roadblocks faced since the promulgation of the 2010 Constitution. In doing so, it primarily employs a doctrinal research methodology analysis. It is argued that an obscured definition of leadership and integrity and insufficient institutional capacity have slowed down the implementation of Chapter 6. This article proposes minimum statutory penalties, a harmonised understanding of the standards of integrity to be attained and the security of tenure of offices such as special magistrates.